Separation of homogeneous catalysts using Organic Solvent Nanofiltration - Masinda, Thabiso Cyprian (North-West University (South Africa), 2016)
One technology that has shown in literature to have great potential for separating homogeneous catalysts from their reaction mixture is organic solvent nanofiltration (OSN), which is a pressure-driven, membrane-based separation technique. It is used in this study, for the effective separation of new Grubbs-type precatalysts from their reaction mixtures in the metathesis of 1-octene using membranes not studied before to add to the list of membranes that are already reported in literature. Both the metathesis activity and catalyst lifetime of each precatalyst were also investigated. The study was divided into three parts: i) The synthesis of new Grubbs-type precatalysts containing pyridinyl-alcoholato ligands, i.e. benzylidene-chloro[1,3-bis-(2,4,6-trimethylphenyl)-2-imidazolidinylidene]-[1-(2'-pyridinyl)- 1-alkyl-1-phenyl-methanolato]ruthenium with alkyl = isopropyl (1), 4'-methylphenyl (2) or 3'-methylphenyl (3). ii) Activity and lifetime studies of these precatalysts for the metathesis of 1-octene. ii) OSN-separation performance. The pyridinyl-alcoholato ligands and their corresponding Grubbs-type precatalysts were succesfully synthesized and characterized using FTIR, NMR and mass spectrometric techniques. The precatalysts were studied for the metathesis reaction of 1-octene at 80 °C with a catalyst load of 1:7000 (Ru/1-octene molar ratio). Selectivity and turnover numbers (TON) were used to describe the effectiveness of these precatalysts during the metathesis reaction of 1-octene to ethene and 7-tetradecene (primary metathesis products, i.e. PMPs). All the precatalysts showed conversions of the 1-octene to the PMPs of greater than 60% at 80 °C. Precatalyst 1 showed a selectivity of 99,90% and a TON of 5268, while precatalyst 2 and 3 gave a selectivity of 99,83% with a TON of 5983 and a selectivity of 99.85% with a TON of 6401 respectively. In terms of lifetime, the precatalysts showed a decrease in activity after the second addition of 1-octene. Precatalysts 2 and 3 showed a slight decrease to 56% and 66% PMPs ii respectively while 1 showed no activity at all after the second addition of 1-octene. Upon the third addition of 1-octene no activity was observed. The PuraMemTM 280 and PuraMemTM S380 membranes were used for the OSN technique. The permeation performance (flux) and catalyst rejection were determined. Permeation performances with fluxes ranging from 9 to 35 L.m-2.h-1 were obtained for the PuraMemTM series of membranes. The PuraMemTM 280 membrane successfully separated the Grubbstype precatalysts from their post-reaction mixtures at 50 bar, with catalyst rejections >97%. Very poor rejections of the precatalysts were observed with the PuraMemTM S380 membrane
MSc (Chemistry), North-West University, Potchefstroom Campus, 2017
Keywords: 1-octene metathesis; Grubbs-type precatalyst; Organic Solvent Nanofiltration; PuraMemTM.1-okteen; Grubbs-tipe prekatalisatore; Organiese Oplosmiddel Nanofiltrasie; PuraMemTM